ANALYSIS OF FACTORS INFLUENCING THE SELECTION OF BIRTH ATTENDANTS IN THE TALANG MAMAK TRIBE COMMUNITY OF INDRAGIRI HULU DISTRICT: Birth Attendant, Factors - Dona Martilova; Nurmaini; Fikarwin Zuska; Sri Rahayu Sanusi (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
There was a decrease in the maternal mortality rate (MMR) at 390 to 305 out of 100,000 live births but still failed to reach the MDGs target to become SDGs, namely 70 deaths per 100,000 per live birth in 2023. Indonesian data for 2018 based on birth attendants by health workers was 93.1% and non-Nakes 6.7%, there were still 16% who gave birth at home, while in 2022 there were still 3 .65% assisted deliveries by non-health workers.  The purpose of the study was to analyze the factors that influence the selection of birth attendants in the Talang Mamak community of Indragiri Hulu regency. This type of research is quantitative with cross sectional design. The population in this study amounted to 45 respondents with the criteria for respondents, namely pregnant women and mothers who have infants. Data analysis using Chi Square and Logistic Regression.  The results showed that of the 45 respondents, 60% of deliveries were assisted by health workers and 40% were assisted by traditional birth attendants.  There was a relationship between knowledge (p-value = 0.000), attitude (p-value = 0.014), beliefs/practices (p-value = 0.005), cost of labor (p-value = 0.028), distance (p-value = 0.028), family support (p-value = 0.011). The factor that plays the most role in the selection of birth attendants is knowledge with a significant value of 0.025, maternal attitude 0.031 and trust / custom 0.043 and family support 0.054. It is recommended to increase the knowledge of the mother by continuing health promotion with cultural and social approaches, as well as instilling a positive attitude towards health workers as birth attendants, so that childbirth is free of complications.